Nutritional supplementation and elite sports performance (2008)
This paper attempt to critically review and investigate the- role of Nutrition in physical activities and sports performance. The review evaluates the theoretical rationale and potential efforts of athletic performance of carbohydrate, protein and micronutrient supplementation. Carbohydrates are the most efficient fuel for energy production. They can also be stored as glycogen in muscle and liver, functioning as a readily available energy for prolonged strenuous exercise. For an elite athlete the total energy requirement is an average of 4500 calories per day. From previous studies, due to the difficulties of evaluating energy output during sports performance, the calories expended were not stated. Studies of athletes utilizing omega-3 fatty acid and medium – chain tryglycerrided (MCTs) were associated with improvement in metabolic indices. Supplementation with essential vitamins, metabolic intermediates and minerals shows conflicting results, which demands further research. Of the nutrients reviewed, carbohydrates, branched-chain amino acids (BCAA) and creatine appears to have the most nutritional ergogenic potentials for athletes involved in endurance and intense training. All supplements reviewed here need more evaluation for safety and effects on athletic performance